Innovation Diffusion in the Presence of Supply Restrictions - Jain, Dipak; Mahajan, Vijay; Muller, Eitan (Marketing Science, 1991)
Innovation diffusion models are developed to represent the spread of a new product from its manufacturer(s) to its ultimate users. In the marketplace, however, the growth of a new product can be retarded by supply restrictions such as the unavailability of the product due to limitations on the production capacity or difficulties encountered in setting up distribution systems. In the presence of supply restrictions, diffusion models must be developed to capture the dynamics of supply restrictions and to allow management to evaluate the impact of such supply restrictions on the growth of a new product in the market place. Based on the Bass innovation diffusion model, the objective of this paper is to suggest a parsimonious diffusion model that integrates the demand side dynamics with the supply side restrictions. The sensitivity of innovation diffusion patterns in the presence of supply restrictions is examined. An application examining the diffusion of new telephones in Israel is documented to illustrate the usefulness of the proposed model.